COMPARATIVE EVALUATION OF THE COMMON TOXIC PROPERTIES OF THE ANTIBIOTIC AMOXICILLIN OF THE RUSSIAN AND IMPORTED PRODUCTION (EXPERIMENTAL HYGIENIC STUDIES) - Лариса Геннадьевна Горохова; Анна Геннадьевна Жукова (Медицина в Кузбассе)
Russia is implementing an import substitution program in the pharmaceutical industry, which is especially important against the background of a restrictive policy towards the Russian Federation. Amoxicillin is one of the most popular antibiotics; it is represented on the market by both original and generic drugs. At the same time, the safety issues of produced substances for humans, regardless of the manufacture’s company, are vitally important, since the health of the population depends on their intake.